2022
DOI: 10.1007/s10488-022-01207-0
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Mental Health and Trauma-Related Needs of Sheltered Children and Families with Trauma-Focused Cognitive-Behavioral Therapy (TF-CBT)

Abstract: Children and adolescents (“youth”) experiencing homelessness are at a disproportionately high risk of exposure to potentially traumatic events (PTE). However, limited evidence exists as to what interventions are effective when implemented with this high-risk population. The purpose of this study was to (1) document the mental health and trauma-related needs of sheltered youth and their mothers, and (2) examine the feasibility/effectiveness of Trauma-Focused Cognitive-Behavioral Therapy (TF-CBT) administered wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 117 publications
0
3
0
Order By: Relevance
“…For example, time-limited CPP was offered for children from birth to 17 months, time-limited PCIT was offered for children ages 6-7, (time-limited) trauma-focused cognitive behavioral therapy (TF-CBT) was offered for children over the age 7, and referrals were made as appropriate to third-party providers. See Arcia (2020), for details regarding the additional therapeutic services, clinical needs, and outcome data for nonrandomized sample as well as Spiegel et al (2022) regarding the TF-CBT services provided and related outcomes.…”
Section: Methods Participants and Recruitmentmentioning
confidence: 99%
“…For example, time-limited CPP was offered for children from birth to 17 months, time-limited PCIT was offered for children ages 6-7, (time-limited) trauma-focused cognitive behavioral therapy (TF-CBT) was offered for children over the age 7, and referrals were made as appropriate to third-party providers. See Arcia (2020), for details regarding the additional therapeutic services, clinical needs, and outcome data for nonrandomized sample as well as Spiegel et al (2022) regarding the TF-CBT services provided and related outcomes.…”
Section: Methods Participants and Recruitmentmentioning
confidence: 99%
“…Thus, therapeutic success largely depends on the brain's responsiveness and changes in mistrained neural circuits. Some studies have shown the neurological healing effects of creative therapies such as dance/movement, music, drama, and art, which often impact at a non-verbal level involving the limbic system basal ganglia and other areas (Lusebrink 2010, Garrett 2020), while others discuss the effects of trauma-focused cognitive-behavioral therapy (Spiegel et al 2022) on neuroplasticity and the reduction of trauma-related symptoms.…”
Section: Neuroplasticity-a Protector?mentioning
confidence: 99%
“…Understanding these cross-cultural differences is crucial for mental health professionals to provide effective and culturally sensitive care for YEH, as it involves adapting treatment strategies that align with cultural norms [47] in EAP. Although several studies have evaluated the effectiveness of interventions for this population, [48][49][50] there is a lack of understanding of the different mental health interventions and programs for youth homelessness in EAP regions. Most systematic reviews and previous studies have focused on interventions conducted primarily in Western countries.…”
Section: Challenges Of Yeh In Eap and Rationale For The Reviewmentioning
confidence: 99%